2020
DOI: 10.1080/10796126.2019.1704161
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the experiences and dynamics of an unconditional cash transfer for low-income mothers: A mixed-methods study

Abstract: Little is understood about how an unconditional cash transfer might operate and affect behavior among low-income parents of infants in the United States. We investigate these questions using data from a random-assignment pilot study (N = 30) in which unconditional cash transfers were distributed monthly on debit cards to two groups of low-income parents in New York City during the first 12 months of their newborns' lives. Mothers were randomized to receive either $100 per month or $20 per month. Mothers distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…This suggests that in our large and diverse sample, increases in family income, in general, were associated with increases in access to resources and decreases in exposure to adversity. Previous studies have attempted small scale interventions in which the household income of families is supplemented and found relative improvement in the allocation and use of economic resources (Rojas et al, 2020; for a review see Barrientos and DeJong, 2006). We found that income was closely tied to other proximal measures that also showed their unique associations with measures of development.…”
Section: Discussionmentioning
confidence: 62%
“…This suggests that in our large and diverse sample, increases in family income, in general, were associated with increases in access to resources and decreases in exposure to adversity. Previous studies have attempted small scale interventions in which the household income of families is supplemented and found relative improvement in the allocation and use of economic resources (Rojas et al, 2020; for a review see Barrientos and DeJong, 2006). We found that income was closely tied to other proximal measures that also showed their unique associations with measures of development.…”
Section: Discussionmentioning
confidence: 62%
“…This suggests that the development of the hippocampus and the amygdala may be highly sensitive to small variation in income in this low-income sample. Indeed, small fluctuations in income can have substantive effects on a family's ability to meet their needs in low-income contexts (Brownell et al, 2018;Rojas et al, 2020). Consistent with the idea that income variation can be impactful for low-income households, Noble and colleagues have previously shown that the association between income and cortical surface area is most pronounced in low-income children (Noble et al, 2015).…”
Section: Sensitive Periodsmentioning
confidence: 88%
“…While addressing oppression of minority and low-income groups will require large-scale sociopolitical changes, interventions that target systemic inequalities can confer great benefit. For example, regular small unconditional cash transfers to lowincome families improve maternal mental health and reduce depression rates in adolescent boys (115,116). Likewise, animal models suggest that peripubertal environmental enrichment may reverse negative effects of ELA on hippocampal development, HPA-axis reactivity, cognitive functioning, and play behaviors (117)(118)(119).…”
Section: Contextual Factors Affecting Resiliencementioning
confidence: 99%